ANALISIS KORELASI IMPLEMENTASI SISTEM INFORMASI MANAJEMEN TERHADAP TEKNOLOGI INFORMASI DAN KEPUASAN PENGGUNA - Sahfitri, Vivi (Universitas Bina Darma, 2015)
Abstract: Management Information Systems is an Information Technology based management that aims to cater to the needs of the general information of all managers in the company or in the companys organizational subunit. This study examines the relationship between the successful implementation of management information systems to information technology and user satisfaction. The study design used is causal design that aims to examine the relationship between variables in the study. Primary data were obtained through questionnaires as research instruments. Design analysis process carried out through test reliability and validity test to test pernytaan in the questionnaire. Where as to determine the relationship between variables is done through a regression test test test partial and simultaneous. Keywords: Management Information Systems, Information Technology, User Satisfaction